Grass Blade - Ahmad Dweikat; Ibraheem Qadi (My University, 2025)
The project entails designing and implementing Grass Blade, an autonomous robotic system for mowing grassy football areas. Through integrating mechanical, electronic, and software components, it provides efficient and labor-saving solutions for lawn maintenance, with remote control facilities being one of them. Some of its features include obstacle detection and avoidance, adjustable blade height, and a mobile app interface for control. The controller for the Grass Blade robot uses Arduino Mega 2560 with four NEMA 23 stepper motors for walking and a NEMA 17 stepper motor for blade height adjustments. It detects obstacles through ultrasonic sensors, while wireless communication to the phone is facilitated with a Bluetooth module; the app was built with RemoteXY Platform. The robot runs in a manual or automatic mode; in manual mode, the user can control the direction using the app, whereas, in automatic mode, it will navigate on its own using the sensor feedback system. In this automatic mode, it follows a row-based pattern, notices obstacles, overtakes these obstacles by taking any available clear channel, and returns on the row for mowing after this maneuvering. A leadscrew mechanism was chosen for the vertical adjustment of the cutting blades to ensure precision, and buzzers, along with LEDs, were included as safety features to alert users.